PENINGKATAN PEMAHAMAN PENGGUNAAN CAIRAN PEMOTONGAN RAMAH LINGKUNGAN DI BENGKEL LAS DAN BUBUT TRIS PALEMBANG - Muhammad Yanis; Nukman Nukman; Aneka Firdaus; Nova Yuliasari (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Efforts to preserve the environment and natural resources, currently the machining process is directed to apply environmentally friendly machining. One of them is by using cutting fluid from vegetable oil. Vegetable oil as a substitute for mineral oil which is known to be non-renewable, non-biodegradable, carcinogenic, has an impact on health and the environment. This service activity aims to increase knowledge to machine tools for small industrial partners in applying environmentally friendly cutting fluids. The partner workshop is a Tris welding and lathe workshop located in the Kelurahan Kebun Bunga, Palembang. The implementation is carried out in one day with a limited number consisting of partner leaders and employees, other invited participants, and students. Based on the activities carried out, participants' understanding of the material presented increased by 84.4% and specifically material about environmentally friendly cutting fluids achieved the success of 88.9%. Partner workshops are very supportive of the activities carried out and want sustainable activities so that they have an effect on increasing their business.